3D printed wideband flat gain multilayer nonuniform reflectarray antenna for X‐band applications. (5th May 2020) - Belen, Aysu; Güneş, Filiz; Belen, Mehmet A.; Mahouti, Peyman
Abstract: Reflectarray antenna designs have become an efficient solution alternative to their counterpart designs due to their beam scanning capability, low profile, high gain, and mounting flexibility. Herein, design and realization of a wideband, flat gain multi‐layer nonuniform reflectarray (MNURA) using 3D printing technology is presented. Design optimization of the proposed MNURA has been achieved in the two stages: First, a 3D CST Microwave Studio based Multilayer Perceptron Neural Network (MLP NN) model establishes the reflection phase characteristic of the MNURA unit element as an accurate continuous function of the geometrical design parameters and dielectric constant. Then Differential Evolutionary Algorithm DEA is selected as a powerful optimization algorithm for determining the optimum geometrical design parameters and dielectric constant of MNURA throughout the X‐band to have a large range, wideband, and flat gain RA design. 3D printing technology has been used for prototyping of the proposed MNURA design. Here, the resulted optimum dielectric constant value of 2.2 is realized by 56% infill rate of "Polar White" PLA using the relation between the infill rate and dielectric constant. The prototyped antenna has a total size of 300 × 300 (mm), and its measured performance characteristics achieve a wideband flat gain of 23.2 dBi with a ripple level of almost 1.5 dBi and return loss characteristic of less than −10 dB over the operation band of 8 to 12 GHz.